STYLE OF CONTEMPORARY JEWELRY AS A CREATIVE SOURCE - Приходько-Кононенко , І. О.; Полевська, Є. В.; Ганущак-Єфіменко, Л. М. (Art and Design, 2023)
To investigate the characteristic features of the products of Ukrainian jewelers of the contemporary jewelry style; to reveal the peculiarities of the evolution of style and trends in its development for use in the creation of modern author's collections of jewelry. The research methodology includes a literature review, analytical research, interpretation and systematization of the obtained results; while working with visual materials, the visual-analytical method, the method of formal, functional, semiotic analysis was used. Associative and combinatorial design methods were used in the creation of a stylish collection of contemporary jewelry. The results of the research made it possible to identify the peculiarities of the work of contemporary jewelry designers, as well as the factors that determine the functional and cost characteristics of contemporary jewelry. It was determined that as a result of certain transformations of the creative source, it is possible to influence the modern fashion of this design segment, to give a new meaningful load and aesthetic appeal to today's jewelry. Scientific novelty an analysis of projects was carried out in order to determine conceptual directions in the study of the style of contemporary jewelry; approaches to the generalization and typology of design solutions, the systematization of new trends and trends in the development of creative solutions in jewelry art as an exquisite object of design activity based on current creative sources are presented. The practical significance lies in the study of the possibilities of using modern design practices of jewelry for targeted manufacturing in the conditions of individual brands, as well as the creation of sketch proposals of contemporary jewelry style solutions for the further design of a modern women's jewelry assortment in accordance with fashion trends and technologies of their development.